Weight Gain Among Treatment-Naïve Persons With HIV Receiving Dolutegravir in Kenya. (15th December 2022) - Bourgi, Kassem; Ofner, Susan; Musick, Beverly; Griffith, Bradley; Diero, Lameck; Wools-Kaloustian, Kara; Yiannoutsos, Constantin T.; Gupta, Samir K.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Several recent studies have linked integrase strand transfer inhibitors (INSTI) with increased weight gain. Setting: The effects of sex on weight gain with dolutegravir (DTG)-based antiretroviral therapy (ART) among treatment-naïve participants in a lower-income, sub-Saharan population with high rates of pre-ART underweight and tuberculosis (TB) coinfection are unknown. Methods: Our analysis included treatment-naïve participants in Kenya and starting their first treatment regimen between January 1, 2015, and September 30, 2018. Participants were grouped into 2 cohorts based on the initial treatment regimen [DTG vs. nonnucleoside reverse transcriptase inhibitors (NNRTI)]. We modelled weight changes over time using a multivariable nonlinear mixed-effect model, with participant as a random effect. Logistic regression models were constructed to evaluate the association between different variables with extreme increase in body mass index (≥10% increase). Results: Seventeen thousand forty-four participants met our inclusion criteria. Sixty-two percent of participants were women, 6% were receiving active TB therapy, and 97% were on NNRTI-based regimens. Participants starting DTG-based regimens were more likely to gain weight when compared with participants starting NNRTI-based regimens. Female participants starting DTG-based regimens experienced the highest weight gain compared with other participants (mean gain of 6.1 kgs at 18 months). Female participants receiving DTG-based regimens, along with participants with lower CD4 cell counts, underweight at baseline, and those receiving active TB therapy were also at higher risk for extreme body mass index increase. Conclusions: Our study in a lower-income sub-Saharan African population confirms higher weight gain with DTG-based regimens compared with traditional ART for treatment-naïve patients.